2014
DOI: 10.1080/02678373.2014.936922
|View full text |Cite|
|
Sign up to set email alerts
|

The Job Demands-Resources Model in emergency service volunteers: Examining the mediating roles of exhaustion, work engagement and organizational connectedness

Abstract: Using a sample of 887 volunteer emergency service workers in South Australia, we conducted a study based on the JD-R framework to examine the roles of three mediators in the relationship between job characteristics and volunteer well-being. These were (i) exhaustion as a mediator in the relationships between job demands and both poor mental health and turnover intentions; and (ii) work engagement and organizational connectedness as mediators in the relationships of job resources (training and organizational su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 40 publications
4
61
1
5
Order By: Relevance
“…First, the composite measure provides a broader and more holistic representation of exposure to work stressors. Also, using multiple stressor measures as indicators of an overall work demands construct is an approach used almost exclusively among researchers testing the Job Demands-Resources model (e.g., Demerouti, Bakker, Nachreiner, & Schaufeli, 2001; Huynh, Xanthopoulou, & Winefield, 2014). Second, the general goal of this paper is testing two processes that explain how and for whom work stressor exposure is related to alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…First, the composite measure provides a broader and more holistic representation of exposure to work stressors. Also, using multiple stressor measures as indicators of an overall work demands construct is an approach used almost exclusively among researchers testing the Job Demands-Resources model (e.g., Demerouti, Bakker, Nachreiner, & Schaufeli, 2001; Huynh, Xanthopoulou, & Winefield, 2014). Second, the general goal of this paper is testing two processes that explain how and for whom work stressor exposure is related to alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to personality traits, workplace factors also influence individual's professional quality of life (Stamm, 2010). For instance, being connected at work has been associated with fewer symptoms of depression and anxiety (Cockshaw & Shochet, 2010;Cockshaw, Shochet, & Obst, 2013) and burnout (Huynh, Xanthopoulou, & Winefield, 2014). Research has suggested that organisational variables and daily work stressors are more predictive of post-trauma outcomes than individual variables (e.g., personal trauma history, coping strategies; Killian, 2008), but these factors are rarely investigated simultaneously.…”
Section: Individual and Workplace Predictors Of Professional Quality mentioning
confidence: 99%
“…Killian (2008) found that long hours, work drain, and lack of work morale were associated with higher burnout and STS in mental health workers. There is emerging research that sense of belonging in the workplace may mitigate the impact of negative organisational factors in the well-being of mental health workers (e.g., Cockshaw & Shochet, 2010;Huynh et al, 2014). People with a high sense of workplace belonging feel valued, needed, supported, and important to their organisation (Cockshaw & Shochet, 2010).…”
Section: Workplace Belongingnessmentioning
confidence: 99%
“…The current study provides an example of the successful application of the JD-R framework to the volunteer context to better understand antecedents of volunteer engagement, a much-needed research focus (Huynh et al, 2014). The JD-R model provides a simple and flexible framework with which to examine and discuss both negative and positive influences on volunteer engagement.…”
Section: Implications For Theory and Researchmentioning
confidence: 99%
“…Engaged volunteers are also more likely to be satisfied with their volunteer experiences (Huynh, Metzer, & Winefield, 2012), which may lead to them recommending the organization to additional potential volunteers and aid volunteer recruitment efforts. Although interest in volunteer engagement is increasing as evidenced by recent articles on the topic (e.g., Huynh et al, 2014), much investigative work into the antecedents of volunteer engagement remains to be done (Vecina, Chacón, Sueiro, & Barrón, 2012).…”
mentioning
confidence: 99%